Central Asia : exploring insights on gender considerations in climate change - Marina Kovaleva and Walter Leal Filho and Christian Borgemeister and Julia Komagaeva (Sustainability, 2023)
More than three decades of independence of Central Asia (CA) countries have been marked by socio-economic, political, and legal reforms. Growing climate change impacts threaten the wellbeing and livelihood of the already vulnerable local population, more than half of which comprises women. In this context, it is essential to adequately include both women’s and men’s needs in multiple efforts taken by national governments to overcome climate change challenges. This paper explores how gender/women considerations have been already addressed in climate change in CA using bibliometric analysis, an expert-driven assessment approach, and a comprehensive analysis of thematically relevant development projects. The findings demonstrated a significant prevalence of grey literature implying much lower interest from academia. The experts outlined the importance of women’s participation and consideration of their experiences, which were different from men’s, in climate change decision making. The comprehensive analysis of the selected development projects revealed the leadership/empowerment domain of climate change–gender interconnections as being mostly addressed. The implications of this paper regarding the current knowledge on the topic related to the CA region are threefold. Firstly, it highlights a strong need for further scientific research that could be implemented through international research initiatives and national institutional programs. Secondly, it calls for increased input from women representation in climate action at all levels. Thirdly, it outlines areas that require stronger cooperation with international donors to mainstream gender/women considerations among a wide range of stakeholders engaged in climate change and its related fields. Overall, the paper lays a basis for further steps towards advancing gender-sensitive and -responsive approaches in CA, particularly in those climate-change-related areas that are often perceived as being gender-neutral.
Keywords: climate change; gender; Central Asia; women